The use of Problem Based Learning to improve students’ speaking ability - Rizal Fahmi; Asnawi Muslem; Bustami Usman (Universitas Syiah Kuala, 2021)
Speaking skill is one of the basic language skills that has important role for oral communication. This study attempts to find out whether the implementation of Problem Based Learning (PBL) could enhance the students’ speaking skill at Darul Ulum Islamic Boarding, Banda Aceh. The population of this study was the students from the second grade of students at Senior High School Darul Ulum Islamic Boarding, Banda Aceh. The sample of this study was the students in class II-IPA I as experimental group and class II-IPA II as control group. Through the quantitative method, the writer analysed the data by means of t-test.The result shows that there was a significant difference in the students’ speaking skill taught by implementing Problem Based Learning.The students’ mean of pre-test’s score was 51.64. Then in post-test, the mean score of the students was 63.64. In other words, Problem Based Learning has successfully enhanced speaking skill of the II-IPA I students. Therefore, Problem Based Learning may be one of the appropriate teaching methods to improve students’ English-speaking ability as it gives a chance for students to relate themselves with real-life issues that require real-life solutions.